The Problems of A Thai Student in Learning English (A Descriptive Study at English Education Department Student of UIN Prof. K.H. Saifuddin Zuhri) - Aurellia Naela Khilqi; Khairunnisa Dwinalida (Journal of Applied Linguistics (ALTICS), 2022)
This study aims to discover and explain the problems in learning English and to find out the expected support of a Thai student for the studies in English education department of UIN Prof. K.H. Saifuddin Zuhri. The respondent was a Thai EFL student with four years of study abroad experience at UIN Prof. K.H. Saifuddin Zuhri. This research used a descriptive qualitative approach to describe findings based on in-depth interview transcriptions. Miles and Huberman's interactive model analysis was used to analyze the data. This study used data triangulation to ensure the validity of the data. The research result showed that the identified Problems in learning English stated by Mohammed Theory were experienced by a Thai student. This research found that the problems faced by a Thai student in learning English were cultural differences, accent, attitude, environment, grammar, vocabulary and pronunciation. While, other problems experienced beyond the theory mentioned, namely, grasping the lecturer explanation, understanding the learning material and lack of practice. The expected support of a Thai student for the studies at English education department of UIN Prof. K.H. Saifuddin Zuhri, includes support from lecturers, language courses, counselling during the study period, native speakers and English competition. Keywords: English learning problem, Support, Thai student